2014
DOI: 10.1097/bth.0000000000000028
|View full text |Cite
|
Sign up to set email alerts
|

Volar Plate Fixation of Recalcitrant Scaphoid Nonunions With Volar Carpal Artery Vascularized Bone Graft

Abstract: Chronic scaphoid fracture nonunion continues to present a significant challenge to the treating orthopedic surgeon. Internal fixation with threaded compression screws leads to high union rates, and is currently the gold standard, but there are certainly circumstances where a scaphoid screw does not provide the stability necessary for nonunion repair. Results using a volar buttress plate have been promising, but have not been described in conjunction with the use of vascularized bone graft. Vascularized bone gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Thirty-four cases of volar plate fixation of scaphoid nonunion with vascularized or iliac crest bone graft have been described among Dodds et al, Ghoneim, and Leixnering et al Those authors report two failed union among these 34 cases. 5,12,13 For biomechanical reasons alone, the authors propose that locking plate fixation should be considered at least equivalent to screw fixation for scaphoid nonunion. Based on the superior performance of locking plates in simulated osteoporotic bone, and other clinical considerations, the authors believe that locking plate fixation merits consideration in cases of scaphoid nonunion with segmental defect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty-four cases of volar plate fixation of scaphoid nonunion with vascularized or iliac crest bone graft have been described among Dodds et al, Ghoneim, and Leixnering et al Those authors report two failed union among these 34 cases. 5,12,13 For biomechanical reasons alone, the authors propose that locking plate fixation should be considered at least equivalent to screw fixation for scaphoid nonunion. Based on the superior performance of locking plates in simulated osteoporotic bone, and other clinical considerations, the authors believe that locking plate fixation merits consideration in cases of scaphoid nonunion with segmental defect.…”
Section: Discussionmentioning
confidence: 99%
“…11 Recently, plate fixation has been described as a surgical option when nonunion occurs after screw fixation, when a nonunion presentation is delayed >2 years, where there is bone loss, or where screw purchase is suboptimal with a segmental bone defect. 12 Some authors have suggested that scaphoid plating may provide superior fixation in cases of avascular necrosis of the proximal pole. 12 These plates act as bridging plates and may be fixed with either locking or nonlocking screws.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The use of plates to treat the nonunion of the scaphoid has been described previously. [11][12][13][14][15] There are numerous factors that can adversely affect the outcome of surgery for scaphoid nonunion. Besides the radiological and anatomical aspects such as a sclerotic nonunion, humpback deformity, and the vascularization of the proximal fragment, certain patient characteristics, such as age, smoking, and occupation adversely affect the outcomes of surgical treatment.…”
mentioning
confidence: 99%